Reflections on leadership during the Covid pandemic. Issue 7 (3rd October 2021) - Gerada, Clare
ABSTRACT: Doctors lead, in and out of the clinical environment, from ward to board; their roles will range from dealing with risk and uncertainty, communicating with different audiences and managing crises. At the heart of leadership is the ability to make decisions; which operation to perform or treatment to give or, as during this pandemic, what policy to implement or vaccines to order. If leadership is about making decisions, successful leadership is the ability to make the right decisions. This, after all, is what distinguishes a good leader from a poor one. During this pandemic we have been able to compare different leaders, drawn from across the health, political and other sectors. This article identifies how leaders behaved during this pandemic and importantly what can be learnt from their actions.